Ratio Decidendi Putusan PTUN Nomor 25/G/2015/PTUN-Mdn Dalam Pengujian Wewenang Dalam Peradilan Tata Usaha Negara - Islami , Syafiq Ijlal; Giosefi , Muhamad; H. Isep H. Insan, SH.,MH (PT. Sharia Journal and Education Center, 2024)
Abstract This research aims to explore the role of family in children's character building through informal education. Using the Library Research method, this study collected and analysed data from reliable sources in the library including books, journals, and electronic documents. The main focus is on how parents help shape good attitudes and values in children, with a case study on Maudy Ayunda's family who is known to educate children with the principles of independence, hard work, and empathy. The results show that parents play a critical role as the main model in character education, which includes value formation, religious education, and behavioural supervision. Character education in Indonesian schools is still at the introductory stage and has not yet reached the stage of value internalisation, so informal education at home is very significant. This research confirms that effective character education requires co-operation between formal and informal education, with parents as the primary educators. Character building is not only about instilling moral values, but also preparing children to face challenges with responsibility and integrity. Keywords: Character Education, Family, Quality Character Abstrak Penelitian ini mempunyai tujuan untuk menilai sejauh mana UU No. 30 Tahun 2014 yang mengatur mengenai Administrasi Pemerintahan berkontribusi untuk menyelesaikan konflik administratif antara warga dan pemerintah melalui PTUN. Fokusnya adalah untuk mengukur seberapa efektif UU tersebut dalam melindungi publik dari penyalahgunaan kekuasaan oleh pejabat negara. Pendekatan yang diambil adalah analisis kasus, dengan mempertimbangkan keputusan PTUN No. 25/G/2015/PTUN-MDN sebagai studi kasus utama. Temuan dari penelitian ini menunjukkan bahwa pengadilan menolak argumen pembelaan dari tergugat dan memutuskan bahwa tindakan Kepala Kejaksaan Tinggi Sumatera Utara dalam menerbitkan Surat Panggilan tanpa berkoordinasi dengan APIP merupakan pelanggaran terhadap UU Administrasi Pemerintahan. Hasil ini menegaskan bahwa UU Administrasi Pemerintahan telah efektif dalam mengatur perilaku pejabat pemerintah agar tidak menyimpang dari prosedur hukum yang ditetapkan. Adapun kesimpulannya adalah bahwa implementasi UU Administrasi Pemerintahan oleh PTUN ini meningkatkan perlindungan hukum bagi masyarakat terhadap penyalahgunaan kekuasaan terhadap wewenangnya oleh pejabat pemerintah. Kata Kunci : Penyalahgunaan Wewenang, Pejabat Pemerintahan, PTUN